ANALYSIS OF DIARRHEA EVENTS IN POST-EARTHQUAKE BALINES IN THE WORKING AREA OF WEST ALKESMAS ALAS BARAT DISTRICT SUMBAWA DISTRICT YEAR 2018 - Hamdan (Yayasan Pendidikan Medika Indonesia, 2020)
Diarrhea is the second leading cause of death in children under five years, around 760,000 children die each year from diarrhea. Most of them have diarrhea caused by eating and sources of water contaminated with bacteria and viruses. 780 million people do not have access to drinking water and 2.5 billion people do not have sanitation. Diarrhea due to infection is widespread in all developing countries. Most people who die from diarrhea due to severe dehydration and loss of fluid (WHO, 2013). This study aims to determine the analysis of diarrhea events in post-earthquake toddlers in the Alas Barat Community Health Center Working Area in Alas Barat Subdistrict, Sumbawa Regency in 2018 This research is quantitative and qualitative using Cross Sectional design using primary and secondary data. The results showed that the proportion of diarrhea was 61 (67.8%), most had complete immunization status (67.8%), Good Nutrition Status (70.0%), no LBW (70.0%), Exclusive breastfeeding (92, 2%), and Cleanliness of Toddlers is not clean (62.2%), mother's education level is low (64.4%), does not wash hands with soap (68.9%), mother's age ≤ 30 years (61.1%), availability food and beverages not available (52.2%), solid occupancy density (75.6%), less clean sanitation (72.2%), latrine unavailability (70.0%), unavailability of clean water (53.3%), close access to health services (60.0%), and the role of health workers who play a role (70.0%) so that it can be seen that affecting diarrhea in infants including: LBW, toddler hygiene, maternal education, hand washing habits with soap, availability of food, sanitation, latrine availability, availability of clean water. Suggestion It is hoped that it can improve counseling to the community on how to prevent and cope with diarrheal diseases in toddlers in the community, and explain to the community, especially mothers of toddlers about the causes of diarrhea that can be caused by various factors and explain to the community about the importance of maintaining environmental sanitation, washing hands before eating, hygiene of toddlers, maintaining cleanliness of latrines to avoid various diseases, especially diarrheal diseases after the earthquake on Sumbawa